Energy security index of Pakistan (ESIOP). (November 2021) - Abdullah, Fahad Bin; Iqbal, Rizwan; Jawaid, Mohammad; Memon, Imran; Mughal, Shoaib; Memon, Falak Shad; Ali Rizvi, Syed Safdar
Abstract: This study presents an assessment of Pakistan's energy security performance by measuring its Energy Security Index (ESIOP) for the years 1991–2040. The ESIOP consists of 39 indicators finalized by discrimination analysis, reliability testing and weighted through principal component analysis (PCA). On the basis of results, Pakistan's energy security performance shows a declining trend at a moderate level between 1991 and 2020 followed by an upward trend until 2040. The analysis shows that Pakistan's current policy is not effective in improving performance owing to its high import dependence and governance issues. As a result, Pakistan is vulnerable, therefore appropriate means of identifying risks in the energy mix and their correlation in energy planning and energy security may be improved upon. Highlights: Pakistan's energy security performance is measured by Energy Security Index (ESIOP) for the years 1991–2040. The ESIOP consists of 39 indicators and standardized using the z-score method. Indicators are weighted on the basis of principal component analysis (PCA). ESIOP shows a declining trend at a moderate level between 1991 and 2020 followed by an upward trend until 2040.